A Design style for geospatial data representation: Technical guidelines - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
These guidelines and procedures have been developed consistent with the CGIAR Principles on the Management of Intellectual Assets and by the CGIAR’s commitment to Open Access and they explain how to implement the geospatial data style for presentation and mapping. This technical guide describes the practical implementation of geospatial data symbology in data publication and dissemination including that used in the FTA’s geoportal.